Samurai rising : the epic life of Minamoto Yoshitsune - Turner, Pamela S. (Charlesbridge, 2018)
Highlights the life and samurai career of Minamoto Yoshitsune. When fifteen-year-old Yoshitsune escapes the monastery he'd been exiled to, he trained to become a great warrior and soon set out with his half brother to rise up against the most powerful samurai in Japan.